Можливості економічного розвитку на засадах циркулярності в умовах цифрової трансформації - Горбаченко, С. А.; Клєвцєвич, Н. А. (Запоріжжя : Класичний приватний університет, 2023)
У статті встановлено, що останнім часом світова економіка розвивалася та функціонувала в лінійному форматі, сутність якого полягала в тому, що все що надавала природа становило базу для ресурсів виробництва, потім з цього вироблялися товари, які ставали відходами після їх використання. Зроблено висновок, що така світоглядна економічна модель сьогодні загрожує нормальному існуванню всього людства, яке наразі споживає природних ресурсів на порядок більше, ніж може відновити. Доведено, що циркулярна економіка змінює це докорінно. Визначено, що для розповсюдження цих рішень у глобальному вимірі та в різних галузях необхідно створювати відповідні цифрові основи. Зроблено висновок, що без зусиль із цифровізації досягнення циркулярності економічного розвитку буде неможливим. Без цифрових рішень перехід до циркулярної економіки відбуватиметься повільніше, з меншою кількістю привабливих бізнес-моделей замкнутого циклу та меншим впливом на екологію, економіку та соціум. Цифровізація циркулярної економіки має забезпечувати цифрову основу для замкнутих бізнес-моделей, тим самим скорочуючи витрати, час та ризики.

The article established that recently the world economy developed and functioned in a linear format, the essence of which was that everything provided by nature formed the basis for production resources, then goods were produced from this, which became waste after their use. It was concluded that such a global economic model today threatens the normal existence of all humanity, which currently consumes natural resources an order of magnitude more than it can restore. The circular economy has been proven to fundamentally change this. It was determined that the circular economy is a new concept of economic development that offers the state and entrepreneurs modern innovative approaches to recovery, reuse, rational consumption of materials and provides an opportunity to create additional value. It is aimed at ecologically clean production and consumption, achieving certain economic and social effects. Such a new worldview requires the application of progressive innovative solutions at all stages of the product life cycle. And for this, it is necessary to use new circular business models, which involve the use of a smaller amount of resources for the creation of goods and services, as well as a significant prolongation of the life cycle of existing products and services. It was established that in the global dimension, such a concept is considered as a way to transition to a resource-efficient economy.It was determined that currently most of the initiatives in this area are individual projects that are directed at material resources, therefore, for the distribution of these solutions on aglobal scale and in various industries, it is necessary to create appropriate digital foundations. It was concluded that without digitalization efforts, it will be impossible to achieve the circularity of economic development. Without digital solutions, the transition to a circular economy will be slower, with fewer attractive closed-loop business models and less impact on ecology, economy and society. The digitization of the circular economy should provide a digital basis for closed business models, thereby reducing costs, time and risks.
Горбаченко С. А., Клєвцєвич Н. А. Можливості економічного розвитку на засадах циркулярності в умовах цифрової трансформації / С. А. Горбаченко, Н. А. Клєвцєвич // Держава та регіони. Серія: Економіка та підприємництво. – Запоріжжя : Класич. приват. ун-т, 2023. – № 1 (127). –С. 35-41. Режим доступу : http://www.econom.stateandregions.zp.ua/journal/2023/1_2023/7.pdf
Keywords: циркулярна економіка; економіка замкнутого циклу; циркулярний економічний розвиток; цифровізація; цифрова трансформація; circular economy; closed cycle economy; circular economic development; digitalization; digital transformation